Europäische Währungsunion: schlecht gerüstet für große Krisen; European Monetary Union: Badly prepared for big crises - Michael Heine; Hansjörg Herr (Wirtschaftsdienst, 2021)
Bereits vor der Corona-Krise zeigte die Europäische Währungsunion (EWU) eine unbefriedigende wirtschaftliche Entwicklung mit niedrigem Wachstum und zu geringer Inflation. Zur Krisenbekämpfung ist die Koordination zwischen Geld- und Fiskalpolitik notwendig. Unzureichende Lohnsteigerungen, die zu Deflation führen, müssen vermieden werden. Nicht zuletzt ist ein Mechanismus zur Stabilisierung des Finanzsystems und zum schnellen Umgang mit notleidenden Krediten erforderlich. Abgesehen von der Geldpolitik fehlt es der EWU an Institutionen, welche die notwendige Wirtschaftspolitik unterstützen. Es besteht somit die Gefahr einer langfristigen Stagnation in der EWU. – – Even before the COVID-19 crisis, the European Monetary Union (EMU) exhibited an unsatisfactory economic development with low growth and inflation rates below the target rate of the central bank. Macroeconomic coordination among monetary and fiscal policy is necessary to fend off such large crises. Insufficient wage increases that lead to deflation need to be avoided. Last, but not least, a mechanism is needed to stabilise the financial system and quickly deal with non-performing loans. Except in the field of monetary policy, the EMU lacks institutions that support quick and sufficient economic policies. There is the danger that policy mistakes will lead to long-term stagnation in the EMU or possibly even a great recession.
Keywords: E6; H12; J3; 330